Penggunaan Media Permainan Ular Tangga Digital dalam Pembelajaran Bahasa Indonesia Kelas 4 Materi Teks Narasi untuk Meningkatkan Motivasi Belajar Peserta Didik: Penelitian - Winda Tri Utami; Esti Untari; Dwi Windari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to describe the increase in students' learning motivation through the use of digital snakes and ladders game media in learning Indonesian language narrative text material in grade IV of elementary school. The method used is descriptive qualitative with data collection techniques through questionnaires given to 27 grade IVB students of SDN Pengalaman 1 Malang. The questionnaire instrument consists of 25 statement items covering four aspects: student involvement, understanding of the material, learning motivation, and ease of use of the media. The results of the analysis showed that the average score of student involvement was 3.80 (very good category), understanding of the material 3.40 (very good category), learning motivation 3.60 (very good category), and ease of use of the media 3.20 (good category). These findings indicate that digital snakes and ladders game media contributes positively to increasing students' learning motivation and involvement. The use of innovative media like this has been proven to create a more enjoyable, interactive, and meaningful learning atmosphere.